SEJARAH SISTEM PENDIDIKAN ISLAM DI KUALA LUMPUR (History of Islamic Education System in Kuala Lumpur) - Sahad, Mohd Nizam; Sa’ari, Che Zarrina (Journal of Al-Tamaddun, 2011)
This article is based on a qualitative descriptive study using the methods of documentation, interviews and observation. It discusses the history of Islamic education in Kuala Lumpur through the presentation of the history of Kuala Lumpur and its Malay community. Later discussions focus on the history of the early development of Islamic education in this city, while concentrating on the period prior to the independence of Malaya. Further development of Islamic education in the post-independence period in the city is explained with an emphasis on the historical role of institutions of formal and non formal education. The results show that there exist ongoing efforts in the Malay community to ensure the survival of Islamic education system in Kuala Lumpur. These can be seen as positive developments in the Islamic education system of Kuala Lumpur.